Analyzing Reading Comprehension Questions in English Textbooks Using Barrett’s Taxonomy - Riry, Jholie Grace Imanuella; Binnendyk, Sophia (MATAI: International Journal of Language Education, 2025)
This study analyzes reading comprehension questions in the English textbook “Bahasa Inggris Tingkat Lanjut” using Barrett’s Taxonomy. The objective is to categorize and evaluate the cognitive demands of these questions, providing insights into the effectiveness of the textbook in developing students' reading comprehension skills. Through a qualitative content analysis of the questions, the study identifies the distribution of questions across the five levels of Barrett’s Taxonomy: Literal Comprehension, Reorganization, Inferential Comprehension, Evaluation, and Appreciation. The findings reveal a disproportionate distribution of cognitive levels questions in this textbook. There are 6 (14%) literal comprehension, 1 (3%) reorganization question, 19 (45%) inferential questions, 11 (26%) evaluation questions, and 5 (12%) appreciation questions. The analysis suggests that the textbook moderately promotes higher-order thinking skills, but lacks a balanced distribution recommended by educational standards. The study underscores the need for a more varied approach to question design in textbooks to foster comprehensive reading skills. Implications for educators, textbook authors, and curriculum designers include the necessity to incorporate a wider range of question types to better support students' cognitive and interpretive abilities. Future research should explore the impact of diversified questioning techniques on student learning outcomes across different educational contexts. Future editions of the textbook should include more balanced distribution of questions types, reducing the proportions of Essay question and increasing the number of multiple choices questions. The textbook also should include more types of questions, such as, Yes/No, True/False and WH questions.